The effect of zinc supplementation on polymorphonuclear leukocyte functions of elder hypertensive patients and healthy young volunteers - (:unkn) unknown (My University, 2009)
Zinc supplementation can stimulate polymorphonuclear leukocyte (PMN) functions (phagocytosis and intracellular killing activity) in older hypertensive patients and healthy young volunteers. The aim of this study is to investigate the effect of zinc supplementation on polymorphonuclear leukocyte (PMN) functions (phagocytosis and intracellular killing activity) in vitro in 13 older hypertensive patients and compare these functions with those of 10 healthy young volunteers. PMNs were isolated by ficoll-hypaque gradient centrifugation method from venous blood with EDTA (0.1g/ml).Phagocytosis and intracellular killing activity were assayed by modifying Alexander's method. The subjects were given zinc supplementation 22mg/daily/30 days. Serum zinc levels were measured by flame atomic absorption spectrometer. The serum zinc levels and the PMN's intracellular killing activities of older hypertensive patients before zinc supplementation were significantly low when compared with that of healthy young volunteers (p<0.001, p=0.001 respectively). After zinc supplementation the PMN's phagocytic and intracellular killing activities of older hypertensive patients were significantly lower than those of healthy young volunteers (p<0.001, p<0.05 respectively). However the serum zinc level of the elderly increased after zinc supplementation when compared with that before supplementation . The serum zinc levels and PMN's phagocytic activity of healthy young volunteers significantly increased after zinc supplementation (p<0.05). Consequently, the serum zinc levels of the older hypertensive patients and young volunteers increased after zinc supplementation. Adequate zinc supplementation may improve PMN functions both in older hypertensive patients and healthy young volunteers.
Keywords: Intracellular killing; Older hypertensive patients; Phagocytosis; Polymorphonuclear leukocyte functions; Zinc supplementation